2017
DOI: 10.2172/1351153
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Cost and Performance of Photovoltaic Systems as a Function of Module Area

Abstract: We investigate the potential effects of module area on the cost and performance of photovoltaic systems. Applying a bottom-up methodology, we analyzed the costs associated with mc-Si and thin-film modules and systems as a function of module area. We calculate a potential for savings of up to $0.04/W, $0.10/W, and $0.13/W in module manufacturing costs for mc-Si, CdTe, and CIGS respectively, with large area modules. We also find that an additional $0.04/W savings in balance-of-systems costs may be achieved. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 10 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Importantly, the labor cost for installing and replacing modules is only a miniscule fraction of the total system cost. 22 We use a typical breakdown of the total labor cost-50% structural and 50% electrical-where module installation accounts for one-seventh of structural labor and inverter installation accounts for one-tenth of electrical labor.…”
Section: Technoeconomic Modeling Of Module Replacement Using Us Pv Symentioning
confidence: 99%
“…Importantly, the labor cost for installing and replacing modules is only a miniscule fraction of the total system cost. 22 We use a typical breakdown of the total labor cost-50% structural and 50% electrical-where module installation accounts for one-seventh of structural labor and inverter installation accounts for one-tenth of electrical labor.…”
Section: Technoeconomic Modeling Of Module Replacement Using Us Pv Symentioning
confidence: 99%
“…These studies helped a customer to choose a reliable tool for PV planning and design from the system point of view, without depending on the equipment supplier. The authors of References [7][8][9] studied the PV cost of the residential application of a PV system in terms of energy payback time (EPBT) and energy return on energy investment (EROI). They found that the small PV modules area helps to increase the energy yield but it increases the model-level and system-level cost per watt.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve ultimate grid parity, the cost of PV installation should meet SETO's SunShot 2030 cost targets of $0.03/W for utility and approximately $0.04/W for residential PV installations. 4 When considering the total cost of PV installation, CIGSe PV cost modeling showed significant potential for advantageous cost over large areas, and through decreased materials which contributes about 18% to the cost of modules. 5 Non-vacuum material deposition techniques such as ink jet printing 6 or spray and paste 7 coating applicable to CIGS nanoparticle are expected to reduce manufacturing costs compared to traditionally used sputtering techniques.…”
Section: ■ Introductionmentioning
confidence: 99%